PENGARUH SOCIAL MEDIA PROMOTION, PRICE DISCOUNT, DAN SERVICE QUALITY TERHADAP LOYALITY MELALUI PURCHASE DECISION SEBAGAI VARIABEL INTERVENING PADA UMKM LALABEADS DI BONDOWOSO - Feby Eka Nur Yuliana; Ika Wahyuni; Muhammad Iqbal Anshory (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the influence of social media promotion, Price Discounts, and Service Quality on Loyalty with Purchase decisions as intervening variables at LALABEADS UMKM in Bondowoso. This study uses a quantitative approach with a survey method by distributing questionnaires to LALABEADS consumers. The data analysis was carried out using the Partial Least Square (PLS) method. The results showed that social media promotion had a negative but not significant effect on purchase decisions. The price discounts and service quality had a significant negative effect on Purchase Decisions. In addition, social media promotion also had a negative but not significant effect on Loyalty. In the indirect path, Social media promotion and price discounts have a negative but insignificant effect on Loyalty through Purchase Decisions. Conversely, Service quality has a significant positive effect on Loyalty through Purchase Decisions. This finding indicates that service quality has an important role in driving Loyalty through Purchase Decisions, while Social media promotion and price discounts have not provided an optimal effect.